Finding value of $\displaystyle \sum^{\infty}_{k=0}\frac{(-1)^k}{\bigg(1\cdot 3 \cdot 5\cdots \cdots (2k+1)\bigg)\cdot 2^k}$

Try: We can write it as $$\sum^{\infty}_{k=0}\frac{(-1)^k\cdot\bigg( 2\cdot 4 \cdot 6\cdots (2k)\bigg)}{\bigg(1\cdot 2 \cdot 3\cdots (2k+1)\bigg)\cdot 2^k}=\sum^{\infty}_{k=0}\frac{(-1)^k\cdot 2^k\cdot k!}{(2k+1)!\cdot 2^k}$$

So we have $$\sum^{\infty}_{k=0}\frac{(-1)^k\cdot k!\cdot (k+1)!}{(2k+1)!\times (k+1)!}=\sum^{\infty}_{k=0}\frac{(-1)^k}{\binom{2k+1}{k}\cdot (k+1)!}$$

Now i did not understand how to solve further

Could some help me , Thanks


Rewriting the sum as $$2\sum_{k=0}^\infty\frac{(-1)^k2^k}{(2k+1)!!}\left(\frac12\right)^{2k+1}$$ we see the Maclaurin series of the Dawson integral, with argument $\frac12$: $$=2F\left(\frac12\right)=\sqrt\pi e^{-\frac14}\operatorname{erfi}\left(\frac12\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.